STRATEGI EFEKTIF MENINGKATKAN KUALITAS DAN MUTU KERJA STAFF DI HOTEL MORISSEY JAKARTA - Iskandar, Hari (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2026)
The hospitality industry faces challenges in improving staff performance to maintain optimal service standards. This Community Service Program (PKM) aimed to enhance the quality and performance of Hotel Morissey Jakarta staff through training in technical skills and soft skills. The methods used in this program included interactive training, group discussions, and case studies relevant to the hospitality industry. This program involved 25 participants from various departments, and the results indicated a significant improvement in their understanding of time management, conflict resolution, and effective work strategies. Evaluation results showed that 85% of participants gained new insights applicable to their daily tasks. Additionally, the collaboration between academia and the industry in this training opened opportunities for further partnerships in hospitality human resource development. This program demonstrated that a practice-based and participatory training approach effectively enhances staff skills and work motivation. For sustainable results, continuous training and evaluation are needed to ensure ongoing improvements in hospitality service quality